Hospital Nursing Staff Perceptions of Resources Provided by Their Organizations During the COVID-19 Pandemic. (April 2021) - Cho, Hyeonmi; Sagherian, Knar; Steege, Linsey M.
Background: The coronavirus disease 2019 (COVID-19) pandemic has profoundly impacted the health and psychological well-being of hospital nursing staff. While additional support is needed to better cope with increased job stressors, little is known about what types of hospital resources have been provided and how nursing staff perceive them. This study addressed this gap by describing nursing staff perceptions of resources provided by hospitals during the COVID-19 pandemic in the United States. Methods: Registered nurses and nursing assistants who were working in hospitals during the pandemic were recruited to an online survey via social media posts and emails between May and June 2020. A total of 360 free-text responses to an open-ended survey question were analyzed using content analysis. Results: Over half of participants reported being provided with hospital resources. "Basic needs" resources that included food on-site, groceries, and childcare support were the most frequently reported compared with four other types of resources (personal health and safe practice, financial support, managerial support, communication). Four themes emerged related to staff perceptions of support: community support, unequal benefits, decreasing resources, and insufficient personal protective equipment. Conclusion: Our findings can assist organizational leaders in the planning and allocation of different types of resources that are meaningful to nursing staff and thus ensure sustainability, optimal performance, and worker well-being during crises.